Temporal transcriptome of tomato elucidates the signaling pathways of induced systemic resistance and systemic acquired resistance activated by Chaetomium globosum - Singh, Jagmohan; Aggarwal, Rashmi; Bashyal, Bishnu Maya; Darshan, K.; Meena, Bharat Raj; Yadav, Jagdish; Saharan, M. S.; Hussain, Zakir (Frontiers in Genetics, 2022)
Chaetomium globosum is an endophytic fungus, which is recorded effective against several fungal and bacterial diseases in plants. The exclusively induce defense as mechanism of biocontrol for C. globosum against phyto-pathogens is reported. Our pervious study states the effectiveness of induced defense by C. globosum (Cg), in tomato against Alternaria solani. In this study the temporal transcriptome analysis of tomato plants after treatment with C. globosum was performed for time points at 0 hpCi, 12 hpCi, 24 hpCi and 96 phCi. The temporal expression analysis of genes belonging to defense signaling pathways indicates the maximum expression of genes at 12 hrs post Cg inoculation. The sequential progression in JA signaling pathway is marked by upregulation of downstream genes (Solyc10g011660, Solyc01g005440) of JA signaling at 24 hpCi and continued to express at same level upto 96 hpCi. However, the NPR1 (Solyc07g040690), the key regulator of SA signaling is activated at 12 hours and repressed in later stages. The sequential expression of phenylpropanoid pathway genes (Solyc09g007920, Solyc12g011330, Solyc05g047530) marks the activation of pathway with course of time after Cg treatment that results in lignin formation. The plant defense signaling progresses in sequential manner with time course after Cg treatment. The results revealed the involvement of signaling pathways of ISR and SAR in systemic resistance induced by Cg in tomato, but with temporal variation.